The whole story alternative medicine on trial? - Murcott, Toby (Macmillan, 2005)
"The Whole Story rounds up the latest evidence on the placebo effect, the randomized control trial, personalized genetic medicine, acupuncture, homeopathy, osteopathy and more and comes to an unexpected conclusion: alternative therapies could provide valuable new ways to help chronic diseases. Biochemist and science journalist Toby Murcott invites conventional medicine to drop its prejudices and investigate these treatments rigorously in pursuit of powerful new approaches to healthcare."